Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran PAIKEM Pada Pembelajaran Bahasa Indonesia Di SD Negeri 054904 Lorong Bambuan - Ajeng Dwi Kartika; Cinta Zahra Dwi Putri Br. Purba; Tri Wantini (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research aims to improve student learning outcomes at SD Negeri 054904 Lorong Bambuan. This type of research is classroom action research (PTK). Classroom action research consists of two cycles. Each cycle consists of four stages that must be passed, namely planning, implementation, observation and reflection. This research was conducted at SDN 054904 Lorong Bambuan. The research was carried out from 18 October 2023 to 18 December 2023 for the 2023/2014 academic year. The research subjects were 19 class V students consisting of 11 female students and 8 male students. The research object is the PAIKEM method. Data collection techniques are observation, questionnaires and tests. Based on the research results, it can be concluded that: (1) Student learning outcomes before the action only achieved 21% completeness or as many as 4 students. (2) Student learning outcomes after implementing the Paikem Learning Strategy in cycle I were 47.4% or 9 students completed. Student learning outcomes in cycle II were 100% or 19 people completed.